Bioethanol Production via Herbaceous and Agricultural Biomass Gasification Integrated with Syngas Fermentation - Sahar Safarian; Runar Unnthorsson; Christiaan Richter (Fermentation, 2021)
In this paper, a simulation model based on the non-stoichiometric equilibrium method via ASPEN Plus was established to analyze the gasification performance of 20 herbaceous and agricultural biomasses (H&ABs) linked with syngas fermentation and product purification units for ethanol production. The established simulation model does not consider the gasification system as a black box; it focuses the important processes in gasification such as drying, pyrolysis, gasification, and connection with bioethanol production plants. The results for the 20 H&AB options suggest that the specific mass flow rate of bioethanol from 1 kg of biomass input to the unit is in the range of 99–250 g/kg, and between them, the system fed by hazelnut shell biomass remarkably outranked other alternatives by 241 g/kg production due to the high beneficial results gained from the performance analysis. Additionally, a sensitivity analysis was performed by changing operating conditions such as gasification temperature and air-to-fuel ratio. The modeling results are given and discussed. The established model could be a useful approach to evaluate the impacts of a huge numbers of biomasses and operating parameters on bioethanol output.